Discursos y símbolos del himno patriótico al 15 de setiembre - Carvajal Araya, María Isabel (2016)
This article focuses on statements and symbols present in the Himno Patriótico al 15 de Setiembre. Using an analysis of messages in these statements, we can see the presence of a liberal ideology that sustains the construction of the Costa Rican state from the late 19th Century. The study shows the presence of great number of symbols, mainly those that mention the flag. At the same time, the highly symbolic nature of this Anthem reinforces the civic image of that time and contributes to the deeper understanding of what were the true reasons for the Anthem's creation.